Effect of Continuous Positive Airway Pressure on Blood Pressure Variability in Patients With Obstructive Sleep Apnea. Issue 11 (1st June 2016) - Pengo, Martino F.; Ratneswaran, Culadeeban; Berry, Marc; Kent, Brian D.; Kohler, Malcolm; Rossi, Gian Paolo; Steier, Joerg
Abstract : Obstructive sleep apnea (OSA) is a common risk factor for cardiovascular disease. Continuous positive airway pressure (CPAP) improves OSA symptoms and blood pressure (BP) control. The effect of CPAP on BP variability (BPV) in patients with and without hypertension treated with autotitrating CPAP (APAP) for 2 weeks was studied. A total of 78 participants (76.9% men, 49% hypertensive, mean body mass index 36.2 [6.9] kg/m 2, age 49.0 [12.9] years) underwent 2 weeks of APAP therapy. Office BP, BPV (standard deviation of three BP measurements), and pulse rate were measured before and after treatment. Systolic BPV (5.3±4.9 vs 4.2±3.4 mm Hg, P =.047) and pulse rate (78.0±14.5 vs 75.5±15.8 beats per minute, P =.032) decreased after treatment, particularly in hypertensive participants. Mask leak was independently associated with reduced changes in systolic BPV ( r =−0.237, P =.048). Short‐term APAP treatment reduced BPV and pulse rate, particularly in hypertensive patients with OSA.